Mathematical model of wave diffraction by the system of stripes with different values of surface impedance - Душкін, В. Д.; Мельник, В. Н. (Київський національний університет імені Тараса Шевченка, 2021)
A mathematical model of diffraction of E-polarized and H-polarized waves on a finite system of not perfectly conducting tapes is obtained. The value of the surface impedance on the two sides of the stripes is different. The initial boundary value problem for the Helmholtz equation with boundary conditions of the third kind was reduced to a system of boundary integral equations. This system of boundary integral equations consists of singular integral equations of the first kind and integral equations of the second kind with a logarithmic singularity. The method of parametric representation of integral operator was used to perform transformations. The values of the physical characteristics of the process are expressed through the solutions of the obtained systems of integral equations. Numerical solution of these equations is performed using a computational scheme based on the discrete singularities method.

Получена математическая модель дифракции Е-поляризованных и Н-поляризованных волн на конечных системе не идеально проводящих лент. Величины поверхностного импеданса на двух сторонах каждой ленты разные. Начальная краевая задача для уравнения Гельмгольца с краевыми условиями третьего рода была сведена к системе граничных интегральных уравнений, состоящий из сингулярных интегральных первого рода и интегральных уравнений второго рода с логарифмической особенностью. Для выполнения преобразований был использован метод параметрического представления интегральных операторов. Значение физических характеристик процесса выражаются через решения полученных систем интегральных уравнений. Численное решение этих уравнений выполняется с применением вычислительной схемы, основанной на методе дискретных особенностей.

Отримано математичну модель дифракції Е-поляризовних та Н-поляризовних хвиль на скінченій системі не ідеально провідних стрічок. Величини поверхневого імпедансу на двох сторонах кожної стрічки різні. Початкова крайова задача для рівняння Гельмгольца з крайовими умовами третього роду  була зведена до системи граничних інтегральних рівнянь, що складається з сингулярних інтегральних рівнянь першого роду та інтегральних рівнянь другого роду з логарифмічною особливістю. Для виконання перетворень було використано метод параметричного подання інтегральних операторів. Значення фізичних характеристик процесу виражаються через розв'язки отриманих систем. Числове розв'язання цих рівнянь виконується із застосуванням обчислювальної схеми, що ґрунтується на методі дискретних особливостей.
Математическая модель дифракции волн на системе лент с различными значениями поверхностного импеданса
Математична модель дифракції хвиль на системі стрічок з різними значеннями поверхневого імпедансу
Keywords: parametric representation of integral operator; system of boundary singular integral equations; discrete singularities method; параметричне подання інтегральних операторів; система граничних сингулярних інтегральних рівнянь; метод дискретних особливостей; параметрическое представление интегральных операторов; система граничных сингулярных интегральных уравнений; метод дискретных особенностей